Decay of the electron density and the electron collision frequency between successive discharges of a pulsed plasma jet in N2. (27th March 2019) - van der Schans, Marc; Platier, Bart; Koelman, Peter; van de Wetering, Ferdi; van Dijk, Jan; Beckers, Job; Nijdam, Sander; IJzerman, Wilbert
Abstract: The decay of the electron density and electron collision frequency between successive discharges in a pulsed plasma jet in N2 feed gas has been investigated using microwave cavity resonance spectroscopy. The method and analysis were adapted to be able to apply this diagnostic to a pulsed plasma jet at atmospheric pressure. The results are compared to a global model. It is shown that the electron density and effective collision frequency can be measured using this technique from about 1 μ s up to approximately 60 μ s after the discharge, where the former time scale is limited by the response time of the cavity and the latter by the detection limit of the setup. Although the data analysis requires an estimation of the plasma volume, which limits the absolute accuracy of the electron density to its order of magnitude, the measured electron densities are in the same range as those predicted by the global model. Additionally, there is a good qualitative agreement in the electron density decay rate between the measurements and the model. Furthermore, it is inferred from the model that the minimum seed electron density required for repeatable guided streamer discharges in a pulsed plasma jet in N2 feed gas is of the order of 10 15 m − 3 .